Introduction of Complementary Foods in a Cohort of Infants in Northeast Italy: Do Parents Comply with WHO Recommendations? - Carletti, Claudia; Pani, Paola; Monasta, Lorenzo; Knowles, Alessandra; Cattaneo, Adriano (Nutrients, 2017)
Timing and type of complementary food in infancy affect nutritional status and health later in life. The objective of this paper was to assess complementary feeding practices, looking at timing, type, and compliance with World Health Organization (WHO) recommendations. Data were obtained from a birth cohort of 400 infants, enrolled in Trieste (Italy) between July 2007 and July 2008 and followed up for three years, using a "food introduction timing table". Five WHO recommendations standards were used to assess parental compliance and associated factors. Thirty seven percent of mothers returned the completed "timing table" up until the child was three years of age. Eighty six percent of infants were already receiving complementary foods at six months. The first food type to be introduced was fresh fruit (170 days from birth, median). Overall, infants shared a very similar diet, which was different from the family diet and characterized by delayed introduction of certain food types. Five percent of parents complied with either all five or only one of the WHO recommendations, 34% with three, and 35% with four. The parents' partial compliance with WHO recommendations is probably due to conflicting information received from different sources. This advocates for national evidence-based guidelines, supported and promoted by health professionals.
Keywords: Adult; Cohort Studies; Dairy Products; Diet; Edible Grain; Female; Follow-Up Studies; Fruit; Humans; Infant; Infant Nutritional Physiological Phenomena; Italy; Logistic Models; Male; Mothers; Patient Compliance; Recommended Dietary Allowances; Socioeconomic Factors; Vegetables; World Health Organization